PRESCRIBING ANALYSIS OF CORTICOSTEROIDS AMONG THE DERMATOLOGY IN-PATIENTS IN A TERTIARY CARE TEACHING HOSPITAL, KARAIKAL, PUDUCHERRY. A PROSPECTIVE OBSERVATIONAL STUDY - C.M.DIVYASHANTHI M.D.; E.MANIVANNAN M.D. (International Journal of Pharma and Bio Sciences, 2014)
Corticosteroids remain the most important and frequently prescribed drugs for cutaneous diseases. This study is an effort to assess the drug prescribing patterns of corticosteroids for various skin diseases, to analyse the rationale behind and also to affirm the physicians’ adherence to dosages and formulations in accordance with the recent guidelines.A prospective analysis of 291 in-patients admitted in the department of Dermatology, Karaikal over a period of one year (January2013-December2013) was carried out to ascertain the pattern of usage of corticosteroids for various dermatological diseases in terms of its potency, frequency, duration and routes of administration. The results were expressed in averages, ratios and proportions.Out of the total 291 prescriptions scrutinized, 60.48% were male and 39.51% were female. The average number of drugs per prescription was 6.37 ± 2.06.The topical preparations prescribed were highly potent steroids like Clobetasol (33.33%), followed by moderately potent like Mometasone (28.24%) and low potent Desonide (14.69%).The various formulations utilized were Lotions (48.02%),followed by creams(30.51%),ointments (14.68%) and paste (6.78%). Oral corticosteroids were prescribed for 77 patients (26.46%), the most of which were for contact dermatitis (32.5%).Among the parenteral corticosteroids prescribed for 14 patients(4.81%) the maximum prescribed were for Eczema (28.56%).Dexamethasone was the only parenteral corticosteroid (4.81%) prescribed as injection.The prescribing pattern of corticosteroids by the Dermatologists was analyzed to appraise the conformity with the guidelines. The usage of steroids through topical, oral and parenteral routes was compliant with the guidelines.